On the presence of giant particles downwind of ships in the marine boundary layer. Issue 6 (24th March 2015) - Sorooshian, Armin; Prabhakar, Gouri; Jonsson, Haflidi; Woods, Roy K.; Flagan, Richard C.; Seinfeld, John H.
Abstract: This study examines large oceangoing ships as a source of giant cloud condensation nuclei ( Dp > 2 µm) due to wake and stack emissions off the California coast. Observed particle number concentrations behind 10 ships exceeded those in "control" areas, exhibiting number concentration enhancement ratios (ERs) for minimum threshold diameters of 2, 10, and 20 µm as high as 2.7, 5.5, and 7.5, respectively. ER decreases with increasing downwind distance and altitude. ER becomes better correlated with ship size variables (gross tonnage, length, and beam) as the minimum size threshold increases from 2 to 20 µm, whereas ship speed has a less distinct relationship with ER. One case study of a container ship shows that there are higher concentrations of sea‐salt tracer species behind it relative to adjacent control areas. These results have implications for cloud properties and precipitation in marine boundary layers exposed to ship traffic. Key Points: Field evidence of giant particle (GCCN) emissions by stack and wake of ships GCCN emissions closely related to ship size, especially for larger particles Evidence of sea‐salt enhancement behind a ship